A Patented Autonomous, Fairness-Driven Academic Timetabling and Student Allocation System with Explainable Decision Logic for Stress-Free Higher Education Management - Habeeb, Akmam Ali (American Journal of Biology and Natural Sciences, 2025)
In higher education institutions, academic scheduling alongside the allocation of students were chronic sources of administrative burden and psychological strain on members of the teaching personnel. This study developed an automated academic management system and its subsequent evaluation concerning automated generation of timetables for lectures and laboratories and equitable and adaptive allocations of students to course sections. System-wide constraints, such as room capacities, instructor availability, course and program structures, and academic calendars, were incorporated into a single multi-dimensional framing of the system as an optimization problem. Scheduling conflicts were eliminated, and teaching workloads were equilibrated and balanced through fairness-aligned scheduling models so that the burden on the psychological wellbeing of the academic staff was minimized. A system-wide mitigation of teaching staff burden was further enhanced by a system feature that allowed for the generation of scheduling, and student allocation decisions to be explained. This transparency and the subsequent reduction of conflicts improved the trust by the institutions in the automated processes. Further rescheduling was done to allow for dynamic and partial changes to the systems. Administrative level instability was reduced as absences of instructors, classroom reallocations, or changes in student enrollment would allow for alterations of elements of the schedule, instead of redoing the whole schedule. Gaps of unproductive time were reduced as high-stress periods of teaching activities were clustered to allow, in other systems of academia, for the periods of teaching to be more flexible in schedule. Stress indicators were measured as teaching activities were clustered to allow for the periods of teaching to be more flexible in schedule. The distribution of administrative time and staff stress to be focused on other systems of academia were also greatly reduced, and the balance of workload was achieved and further schedules were also reduced on the side of administration. Students reported more satisfaction with the clarity of the structure and the changes of the schedule as well. The system also showed to be functioning in the cross-sectional services for single and multiple campuses and were able to be incorporated with the other academic systems. Thus, the system became an automated socially responsive system for educational management.